2001
DOI: 10.1017/s0033291701004524
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of first-onset depression in a population followed from the age of 70 to 85

Abstract: Both the incidence and prevalence of depression increased with age in this longitudinally followed birth cohort, and the incidence was higher in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
78
1
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 34 publications
(54 reference statements)
15
78
1
6
Order By: Relevance
“…Our re ported prevalence of lifetime depression is supported by other studies [23][24][25]. Some studies report lowe r prevalences of lifetime depression but these studies are often retrospective and do not include elderly populations [23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our re ported prevalence of lifetime depression is supported by other studies [23][24][25]. Some studies report lowe r prevalences of lifetime depression but these studies are often retrospective and do not include elderly populations [23].…”
Section: Discussionsupporting
confidence: 77%
“…It has been suggested that lifetime prevalence of mental disorders may be twice as high in prospective versus retrospective studies [26]. Our group reported a comparable incide nce of depression in adults age 70 years and older [25].…”
Section: Discussionsupporting
confidence: 53%
“…The incidence of depression vary from 2 to 140 per 1000 person-years. 16,[40][41][42][43][44] In the Epidemiologic Catchment Area Program study, 40 the incidence of phobic disorder in people aged 65 years and older was 27 per 1000 person-years for males and 55 for females, and the incidence of OCD was 10 per 1000 person-years in females. The incidence of social phobia was 17 per 1000 person-years after age 70 years.…”
Section: Frequency Of Mental Disorders In the Elderlymentioning
confidence: 99%
“…56,64,65 This may reflect that elderly people with depression may exhibit less symptoms than younger people with depresson. 66 The incidence of depression has been reported to increase 43 or be unaffected by age. 44 The prevalence of anxiety disorders is also reported to decrease with age.…”
Section: What Is the Relation Between Age And Frequency Of Mental Dismentioning
confidence: 99%
“…10 On the basis of 3 prospective cohorts followed from birth to 26 years, 11 from 24 to 50 years, 12 and from 70 to 85 years 13 we have estimated that at least one-half the population will experience at least one MDE during their lifetime.…”
Section: Epidemiologymentioning
confidence: 99%